Membangun Karakter Peduli Lingkungan Melalui Penanaman Pohon - muliastrini, ketut erna; Putu Bayu Ariska Putra Gotama; Wayan Yanik Yasmini; I Gede Widiastika (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
Reforestation is an effort to plant trees and plants in places that are considered to be able to grow and develop these plants. The benefits of reforestation are preventing soil erosion, making air quality better, improving air quality, controlling climate, preventing flooding and making the scenery more beautiful and fresh. The role and function of fruit plants for the environment needs to be socialized to the people of Kebung Kauh Village, Sidemen District, Karangasem Regency. This service activity aims to (1) build the character of a community who cares about the environment through planting trees as greening the environment. (2) socializing the roles and functions of fruit trees to the people of Kebung Kauh Village. The method used is training in the form of outreach, procurement of facilities and infrastructure, field assistance or fruit planting and evaluation. The planting activity as a greening of the environment was jointly carried out on June 2 2023 taking place in Kebung Kauh Village, Sidemen District, Karangasem Regency. In its implementation, this activity involved 100 participants consisting of university students, students of SD N 2 Telaga Tawang, and the people of Kebung Kauh Village. Its implementation includes: (1) children's education activities and cleaning the environment in Kebung Kauh Village which will be used as a reforestation location, (2) fruit tree planting activities, and (3) fruit plant maintenance activities. The result of this tree planting activity is the planting of coconut, mangosteen, jepun, and sandat trees in several locations in Kebung Kauh Village on land that requires reforestation in Kebung Kauh Village, Sidemen District, Karangasem Regency.